ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER - Suudyasana, Ayu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the difference of financial performance of banking companies whether it exist or not beforeand after themergeron PT Bank CIMB Niaga Tbk. The sample collection technique has been done by using judgment sampling and a company has been obtained as the research sample i.e.: PT Bank CIMB Niaga Tbk. Meanwhile, the data analysis technique has been done by using paired sample t test which is done by using the SPSS 20.0 program.Based on the result of the analysis of paired sample t test, it can be concluded that there were 5 financial ratios which do not have any significant different i.e.: Debt to Equity Ratio, Dept to Total Asset Ratio, Net Profit Margin, Return on Equity, and Return on Asset before and after merger. It shows that the financial performance of the company does not undergo any significant change in which the decline occurs before and after merger. Moreover, there is one financial ratio which has significant difference i.e.: Current Ratio which shows that the financial performance of the company undergoes significant changes before and after the merger.The financial performance of banking companyof PT Bank CIMB Niaga Tbk, before and after merger shows the decline of financial condition, because the result of the overall calculation of financial ratio shows a declination before and after merger. The implication of this research, generally, shows that the main motive of the company to conduct the merger is economic motive, so the purpose of the merger has not completely fulfilled. Keywords: Financial Performance, Financial Ratio, Merger.